Pemanfaatan Internet Untuk Riset Dan Implikasi Terhadap Riset Akuntansi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT Rapid development of internet technology can influence the way we do research. Yet there are some weaknesses of research by using internet such as anonymity. demography of respondent, accessibility, risk of plagiarism, and reliability, the benefit is obvious. Academic staffs, researchers or students are advantaged since they can use it for referencing tool, on-line database, mailing list and media for sampling dissemination Indeed, this paper discuss the implication of internet development on accounting research since there are a lot of accounting related resources in the web that can be found easily by using on-line database or search engine.